PENGARUH PERCEIVED UBIQUITY, PERCEIVED INFORMATIVENESS DAN PERCEIVED PERSONALIZATION TERHADAP MOBILE APP USEFULNESS PEMASARAN PARIWISATA PROVINSI BANTEN PADA WISATAWAN DOMESTIK - PRASETIO , ARTON BRIYAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this study is to know the influence of Perceived Ubiquity, Perceived Informativeness, and Perceived Personalization to Mobile App Usefulness of Tourism Marketing to Domestic Travelers in Banten Province. The research design used in descriptive research and causality research, in which variables are measured with 5 points Likert scale. This research used primary data which collected by questionnaire. The sampling in the study was accidental sampling and used 100 respondents. The research data is processed with IBM statistic19 as a tool. The result of this research has shown thaton the other hand, Perceived Ubiquity, Perceived Informativeness, and Perceived Personalizationhave any influence toward Mobile App Usefulness.